GPCR Activation States Induced by Nanobodies and Mini-G Proteins Compared by NMR Spectroscopy - Philip Rößler; Daniel Mayer; Ching-Ju Tsai; Dmitry B. Veprintsev; Gebhard F. X. Schertler; Alvar D. Gossert (Molecules, 2020)
In this work, we examine methyl nuclear magnetic resonance (NMR) spectra of the methionine ε-[13CH3] labelled thermostabilized β1 adrenergic receptor from turkey in association with a variety of different effectors, including mini-Gs and nanobody 60 (Nb60), which have not been previously studied in complex with β1 adrenergic receptor (β1AR) by NMR. Complexes with pindolol and Nb60 induce highly similar inactive states of the receptor, closely resembling the resting state conformational ensemble. We show that, upon binding of mini-Gs or nanobody 80 (Nb80), large allosteric changes throughout the receptor take place. The conformation of tβ1AR stabilized by the native-like mini-Gs protein is highly similar to the conformation induced by the currently used surrogate Nb80. Interestingly, in both cases residual dynamics are present, which were not observed in the resting states. Finally, we reproduce a pharmaceutically relevant situation, where an antagonist abolishes the interaction of the receptor with the mini-G protein in a competitive manner, validating the functional integrity of our preparation. The presented system is therefore well suited for reproducing the individual steps of the activation cycle of a G protein-coupled receptor (GPCR) in vitro and serves as a basis for functional and pharmacological characterizations of more native-like systems in the future.